Resource flows to less-developed countries: financial terms and their constraints - Gray, Clive S. (New York : Praeger, 1969)
The book considers the flow of financial resources from economically advanced to less-developed countries and how the terms of repayment on the resource flow effect the performance of that flow in meeting the goal of maximizing the economic growth rate of the recipient countries within a framework of political stability.
Bibliography: p. 293-305.
usc 24/08/18
Loans
Keywords: Finance; Developing countries